Arctic Hydrology, Permafrost and Ecosystems - Yang, Daqing; Kane, Douglas L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book provides a comprehensive, up-to-date assessment of the key terrestrial components of the Arctic system, i.e., its hydrology, permafrost, and ecology, drawing on the latest research results from across the circumpolar regions. The Arctic is an integrated system, the elements of which are closely linked by the atmosphere, ocean, and land. Using an integrated system approach, the book$1 (Bs 30 chapters, written by a diverse team of leading scholars, carefully examine Arctic climate variability/change, large river hydrology, lakes and wetlands, snow cover and ice processes, permafrost characteristics, vegetation/landscape changes, and the future trajectory of Arctic system evolution. The discussions cover the fundamental features of and processes in the Arctic system, with a special focus on critical knowledge gaps, i.e., the interactions and feedbacks between water, permafrost, and ecosystem, such as snow pack and permafrost changes and their impacts on basin hydrology and ecology, river flow, geochemistry, and energy fluxes to the Arctic Ocean, and the structure and function of the Arctic ecosystem in response to past/future changes in climate, hydrology, and permafrost conditions. Given its scope, the book offers a valuable resource for researchers, graduate students, environmentalists, managers, and administrators who are concerned with the northern environment and resources.s
Introduction -- Hydrology -- Permafrost and seasonal frozen ground -- Ecosystems -- Linkage and integration.
Keywords: Polar regions; Hydrology; Climate change; Environmental monitoring; Engineering geology; Engineering$1 (BGeology.s; Foundations; Hydraulics; Physical geography; Polar Geography; Hydrology/Water Resources; Climate Change/Climate Change Impacts; Monitoring/Environmental Analysis; Geoengineering, Foundations, Hydraulics; Earth System Sciences